SOCIOLINGUISTICS (CODE: CODE SWITCHING AND CODE MIXING) - Harya, Trisna Dinillah (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The purpose of this article is to know the study of sociolinguistic in linguistics. Sociolinguistic is study that is concerned in the relationship between language and society with the goal of a better understanding of the structure of language and of how languages function in communication. In language, there is a code. A code is a system that is used by people to communicate with each other. When people want to talk each other, they have to choose a particular code to express their feeling. Related of it, this paper is written based on two points of code namely code switching and code mixing as a means of language variation in sociolinguistic, and it is used in daily activities. Person sometimes mix or switch their language when they communicate to the others both in bilingualism and multilingualism. Bilingual (bilingualism) is a person who uses two languages, while multilingual (multilingualism) is a person who uses more than a language. In other words, there is a situation where speaker deliberately change a code being used, namely code switching from one language to another language, or the situation where the people mix two languages when they speak or communicate with the other.